2004
DOI: 10.17221/5687-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dogs in eco-epidemiology of Lyme borreliosis: a review

Abstract: Borrelia burgdorferi sensu lato, is endemic in most of the regions in Europe. Pathogen circulates in nature involving ticks vector (mainly Ixodes ricinus in Europe) and wide spectrum of reservoir animals like rodents, game animals, birds as well as pets. Considering the close association of a dog and humans, and their similar activities in nature, it is necessary to evaluate the significance of a dog as an important animal in ecology and epidemiology of Lyme borreliosis. Antibody profile in Lyme disease is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
(21 reference statements)
0
11
0
4
Order By: Relevance
“…Disease can be identified by serological methods (IFAT, ELISA, Western Blot etc.) with the help of clinical findings [51,53,54] .…”
Section: Dirofilaria Immitismentioning
confidence: 99%
See 1 more Smart Citation
“…Disease can be identified by serological methods (IFAT, ELISA, Western Blot etc.) with the help of clinical findings [51,53,54] .…”
Section: Dirofilaria Immitismentioning
confidence: 99%
“…It has been reported that Lyme disease is one of the most common disease transmitted by ticks in Europe (2.1-53.7%), Brazil (9.7%) and North America (2.3-76.3%) [13,33,47,48,[54][55][56] . Borrelia burgdorferi is the factor of disease was also isolated from vector Ixodes ricinus species ticks [57][58][59][60] .…”
Section: Dirofilaria Immitismentioning
confidence: 99%
“…Un resultado similar señalaron Bermúdez y Miranda (2011), quienes encontraron que los perros que salían de cacería fueron más propensos a infestarse con garrapatas, incluyendo I. affinis, que los perros que no salían de cacería. Los perros de caza suelen llevar garrapatas infectadas desde la selva hasta el medio ambiente humano, donde las garrapatas hembras ponen sus huevos y los estadios inmaduros se alimentan preferentemente de pequeños mamíferos y roedores (Shimada et al, 2003;Bhide et al, 2004). La presencia de roedores en el área peridoméstica facilita la alimentación de las larvas y ninfas, por lo tanto, ayuda a que la población de garrapatas se establezca (Bhide et al, 2004).…”
Section: Resultados Y Discusiónunclassified
“…Los perros de caza suelen llevar garrapatas infectadas desde la selva hasta el medio ambiente humano, donde las garrapatas hembras ponen sus huevos y los estadios inmaduros se alimentan preferentemente de pequeños mamíferos y roedores (Shimada et al, 2003;Bhide et al, 2004). La presencia de roedores en el área peridoméstica facilita la alimentación de las larvas y ninfas, por lo tanto, ayuda a que la población de garrapatas se establezca (Bhide et al, 2004). Estas ninfas ixodidas tienen una amplia gama de hospederos, incluyendo perros y humanos, y al sufrir la metamorfosis en adultos, se convierten en la principal fuente de infección para los perros (Smith et al, 1993).…”
Section: Resultados Y Discusiónunclassified
“…(Ogden et al, 2006;Solís-Hernández et al, 2015). La detección de Borrelia en perros podría ser un criterio importante para la evaluación del riesgo de la EL en humanos, ya que el perro puede emplearse como indicador epidemiológico para la identificación de nuevos focos de esta enfermedad (Bhide, Travnicek, Curlik, & Stefancikova, 2004;Little, Heise, Blagburn, Callister, & MeadLyme, 2010).…”
unclassified